Hubungan antara Intensitas Penggunaan Media Sosial dan Kesehatan Mental pada Remaja dan Dewasa Muda: A Systematic Review of Empirical Quantitative Studies - Yosua Darmadi Kosen; Syarifah Miftahul Jannah; Adis Apriadi; Muhammad Arifial Asyum; Amadea Jovita Miko Faustin; Rizalya Zahra Nurfitri; Yohana Christanti; Alyssa Feodora Ryanto; Kevin Hersan; Ariyani Sudhamma Welliangan; Chandra Wahyudi; Wilma Adiwijaya; Hana Grace Tondang (Jurnal Studi Pemuda, 2025)
The growing prevalence of social media use among adolescents and young adults has raised concerns about its potential impact on mental health. This study was guided by the hypothesis that higher intensity of social media engagement is associated with adverse psychological outcomes. A systematic literature review was performed in accordance with PRISMA 2020 guidelines by searching Cochrane Library, PubMed, Scopus, Web of Science, Proquest, and Google Scholar for empirical studies published between 2015–2025 involving individuals aged 12–24 years. Twenty eligible articles were analysed, encompassing cross-sectional, longitudinal, and randomized controlled trial designs. The synthesis revealed that excessive social media use, particularly exceeding three to four hours daily, was consistently linked to depression, anxiety, sleep disturbances, emotional dysregulation, loneliness, and increased risk of self-harm or suicidal ideation. Key mediating mechanisms included fear of missing out, negative social comparison, cyberbullying, and poor sleep quality. Conversely, evidence from randomized controlled trials demonstrated that limiting usage to approximately 30 minutes per day or temporary abstinence significantly improved well-being, life satisfaction, and psychological resilience. These findings highlight the importance of targeted preventive strategies, including digital literacy, healthy lifestyle promotion, and structured time management, to mitigate the negative consequences of excessive social media use in adolescents and young adults.